(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2023)
The realm of Customer Relationship Management (CRM) has seen significant improvements with the integration of automation and data analytics. Python, known for its robust data manipulation libraries, offers a seamless experience for handling data in Microsoft Dynamics CRM. This paper aims to serve as a comprehensive guide on how Python can be employed to perform CRUD operations— Read, Update, Insert—on data in Microsoft Dynamics CRM. We delve into the intricacies of using Python’s ’requests’ library for API calls and ’concurrent futures’ for parallel processing, thereby optimizing data manipulation tasks. The paper also presents a performance evaluation showcasing the efficiency gains achieved through these methods. Furthermore, the paper highlights the challenges associated with large-scale data management in CRM systems and proposes Python-based solutions as a scalable and effective approach. The paper concludes with a discussion on the scope of this approach in the broader context of CRM data analytics and automation. The methods and findings presented herein are expected to be of particular interest to data engineers, software developers, and CRM administrators.